Cell attachment and proliferation of osteoblast-like MG63 cells on silk fibroin membrane for guided bone regeneration - Yoo, Chae-Kyung (Maxillofac Plast Reconstr Surg, 2016)
BACKGROUND: The aim of this study is to verify the feasibility of using silk fibroin (SF) as a potential membrane for guided bone regeneration (GBR). METHODS: Various cellular responses (i.e., cell attachment, viability, and proliferation) of osteoblast-like MG63 cells cultured on an SF membrane were quantified. After culturing on an SF membrane for 1, 5, and 7 days, the attachment and surface morphology of MG63 cells were examined by optical and scanning electron microscopy (SEM), cell viability was determined using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and cell proliferation was quantified using 4′,6-diamidino-2-phenylindole (DAPI) fluorescence staining. RESULTS: Optical microscopy revealed that MG63 cells cultured on the SF membrane proliferated over the 7-day observation period. The viability of cells cultured on SF membranes (SF group) and on control surfaces (control group) increased over time (P < 0.05); however, at respective time points, cell viability was not significantly different between the two groups (P > 0.05). In contrast, cell proliferation was significantly higher in the SF membrane group than in the control group at 7 days (P < 0.05). CONCLUSIONS: These results suggest that silk fibroin is a biocompatible material that could be used as a suitable alternative barrier membrane for GBR.